Management of economic activity in the system of internal affairs bodies of Ukraine: issues of efficiency of legal regulation - Liashenko, A. A. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
It should be acknowledged that the issues of legal regulation of economic activity in the system of internal affairs bodies (hereinafter - IAB) have not yet become the subject of due attention of scholars. The level of scientific elaboration of problematic aspects in this area does not meet the current tasks of the State policy and does not allow solving the issues of its development and improvement, which, in fact, has led to the need and relevance of our study. The armed aggression against our country and the introduction of martial law as a special legal regime in Ukraine have led to changes in all spheres of public life, requiring the concentration of efforts of the state and private entities to strengthen the country’s defence capability and the competitiveness of the national economy. However, the guarantees of national security of Ukrainian society, protection of rights, freedoms and legitimate interests of citizens, ensuring the rule of law in all spheres of public life, combating crime, ensuring public safety and order remain the main tasks on the way to preserving and developing statehood in Ukraine, and their successful solution directly depends on the level of material and technical support of state bodies called upon to directly regulate social processes in society. Economic activity of the entities of the internal affairs system is a component of modern economic relations in Ukraine, and it is the State regulatory policy which should ensure efficient use of internal material and organisational resources by them with a view to obtaining additional sources of funding on their own and, as a result, to significant budgetary savings in the period of post-war reconstruction of the country. The article proposes a system-management approach as an effective tool for determining the effectiveness of legal regulation of economic activity in the system of internal affairs agencies. The author provides a brief overview of certain legislative initiatives aimed at reforming the system of internal affairs, and identifies priority measures which will allow to provide an objective assessment of the efficiency of economic activity in the system of internal affairs, outline ways to improve it and ensure further savings and rational use of budgetary funds.